Economic evaluation of "healthy beginnings" an early childhood intervention to prevent obesity. (27th March 2014) - Hayes, Alison; Lung, Tom; Wen, Li Ming; Baur, Louise; Rissel, Chris; Howard, Kirsten
<x xml:space="preserve">Abstract</x> Objective To determine the costs and cost‐effectiveness of an early childhood home visiting program delivered to families in socio‐economically disadvantaged areas of Sydney, Australia during 2007‐2010. Methods Economic evaluation of a randomized controlled trial, the healthy beginnings (HB) trial, from the perspective of the health funder. Intervention resources were determined from local health district records in 2012 AUD. Health‐care resource utilization was determined through patient‐level data linkage. Results The cost of HB intervention in the clinical trial over 2 years was 1309 per child (2012 AUD). The incremental cost‐effectiveness ratio was 4230 per unit BMI avoided and 631 per 0.1 reduction in BMI z‐score. It was estimated that the program could be delivered in practice for 709 per child; with incremental cost‐effectiveness ratios of 2697 per unit BMI avoided and 376 per 0.1 reduction in BMI z‐score. Conclusions We present the first economic evaluation of an effective obesity prevention initiative in early childhood. HB is a moderately priced intervention with demonstrated effectiveness that offers similar or better value for money than existing obesity prevention or treatment interventions targeted at older children.